2009
DOI: 10.2174/1876386300902010053
|View full text |Cite
|
Sign up to set email alerts
|

Selective Stimulation of C Fibers by an Intra-Epidermal Needle Electrode in Humans

Abstract: Abstract:We recorded evoked potentials (EPs) induced by intra-epidermal electrical stimulation using a needle electrode with specific parameters. We identified the fibers activated by this specific stimulation by assessing the conduction velocity (CV) of the peripheral nerve. The EPs were recorded from the Cz electrode (vertex) of the International 10-20 system in ten healthy male subjects. The dorsum of the left hand and forearm were stimulated with an intensity of 0.01 mA above the sensory threshold. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…Unlike with laser stimulation, there is no undesired skin effect, such as heat burn or erythema. The electric stimulus can be a conventional square wave pulse of 0.5∼1.0 ms but a slowly rising pulse, such as a triangular wave,10 is better. Double pulses with a 10∼25 ms interval are usually used to obtain clear responses but a single pulse is also used when a precise response latency is necessary (eg, see Inui et al 11).…”
Section: Intraepidermal Electrical Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike with laser stimulation, there is no undesired skin effect, such as heat burn or erythema. The electric stimulus can be a conventional square wave pulse of 0.5∼1.0 ms but a slowly rising pulse, such as a triangular wave,10 is better. Double pulses with a 10∼25 ms interval are usually used to obtain clear responses but a single pulse is also used when a precise response latency is necessary (eg, see Inui et al 11).…”
Section: Intraepidermal Electrical Stimulationmentioning
confidence: 99%
“…However, the higher density of C nociceptors might be an advantage if the current passing through the concentric electrode is limited to a very small area. In addition, there are several reports of factors that are effective at activating C fibres: a pulse of long duration, a slowly rising pulse, temporal and spatial summation, and anodal stimulation (see Otsuru et al 10). Based on these reports, we tested IES for the selective stimulation of C nociceptors under the following conditions: (1) the anode was the inner needle and the cathode was the outer ring; (2) the electric pulse was a triangular wave with a rise and fall time of 1 ms; (3) the stimulus was a train of three pulses at 50 Hz; and (4) three electrodes 10 mm apart were used 10…”
Section: Stimulation Of C Fibre By Iesmentioning
confidence: 99%
“…Further study will be required to evaluate pain threshold values of small fibres in people with normal glucose tolerance and impaired glucose tolerance. Finally, as Otsuru et al [9] pointed out, a stable stimulation method is still lacking using this type of electrode [9,10], so we also regard the electrode as the primary cause of the low specificity for C-fibre pain thresholds. Recently, Motogi et al [11] reported that a shorter needle expanded the effective range of electric current over which C fibres were selectively stimulated.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, as Otsuru et al . pointed out, a stable stimulation method is still lacking using this type of electrode , so we also regard the electrode as the primary cause of the low specificity for C‐fibre pain thresholds. Recently, Motogi et al .…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of stimulation was 5 Hz, which is expected activate mostly one of the nociceptive afferent fibers: C-fibers, based on fMRI findings [34], and square wave working on pain perception more than sine waveform [35] was used. The other parameters of the waveform were 50 double pulses (bipolar square wave), pulse duration 5 ms, which optimizes for pain perception [36], double pulse interval 95 ms, and inter-stimulus interval (ISI) 1 s [35,37] (Figure 1). Each session contains 50 stimuli, and for each subject, two sessions were conducted with a 5-s pause between the two sessions, resulted in 100 trials, which lasted approximately 2 min in total.…”
Section: Experiments Setupmentioning
confidence: 99%